Infrared up-conversion device based on quantum dots and perovskite thin film

By connecting the infrared spot detector and the perovskite light emitting diode in series in the infrared upconversion device, and using the intermediate layer to improve the energy level matching, the problems of high cost and low efficiency of existing infrared upconversion devices are solved, and the problem of high cost and low efficiency of the preparation of existing infrared upconversion devices is realized. Efficient infrared imaging effect.

CN119170690APending Publication Date: 2024-12-20SHANGHAI TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310737233.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing infrared upconversion devices are cost-effective, require large driving voltages, and have low photon conversion efficiency. Infrared incident light and light-emitting diode emitted light limit their application on the same side, and the resolution depends on the lateral diffusion current, making it difficult to achieve efficient Infrared imaging.

Method used

Using infrared upconversion devices based on quantum dots and perovskite films, the series connection between infrared dot detectors and perovskite light emitting diodes is used to improve energy level matching and carrier transport efficiency, and reduce carriers. Transport transport barriers, and a dense intermediate layer is prepared in combination with evaporation method to improve conversion efficiency.

Benefits of technology

The conversion efficiency of photons to photons is achieved by more than 10%, reducing the working voltage, simplifying the process cost, and achieving high luminance at a smaller current density, and supporting large-area top-emission infrared imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170690A_ABST
    Figure CN119170690A_ABST
Patent Text Reader

Abstract

The invention provides an infrared up-conversion device based on quantum dots and a perovskite thin film and a preparation method of the infrared up-conversion device. The infrared up-conversion device comprises an infrared light spot detector and a perovskite light-emitting diode. The infrared light spot detector and the perovskite light-emitting diode are connected in series through an intermediate layer. The infrared up-conversion device is prepared by a full-solution method, the driving voltage is low, the cost is low, the method is simple, the conversion efficiency of photons on photons on the top side can reach more than 10%, and the infrared up-conversion device has a good application prospect in the fields of infrared detection and imaging devices, biomedical treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photoelectric detectors, and in particular relates to an infrared up-conversion device based on quantum dots and perovskite films and a preparation method thereof. Background Art

[0002] Infrared detection and related imaging technologies are widely used in satellite remote sensing, agricultural crop production, night vision, life science imaging, etc. In particular, the development of autonomous driving, industrial machine vision, and wearable smart devices in recent years has increased the demand for infrared detection and imaging technologies.

[0003] Photon-to-photon up-conversion devices convert low-energy infrared incident light photons into electrons, which then drive the series-connected light-emitting diodes to produce light-emitting displays. Compared to traditional infrared imaging devices, up-conversion devices do not require discrete pixels, and their resolution depends on the lateral diffusion current. In particular, they avoid the expensive indium column welding process, which greatly simplifies the process and reduces costs. However, the infrared up-conversion devices that have been reported are all prepared using expensive vapor phase or epitaxial technology and require a large driving voltage. At the same time, the infrared incident light and the light emitted by the light-emitting diode are on the same side, which limits their application. In addition, the photon conversion efficiency needs to be improved. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide an infrared up-conversion device based on quantum dots and perovskite thin films and a preparation method thereof, so as to solve the problems in the prior art.

[0005] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.

[0006] On the one hand, the present invention provides an infrared up-conversion device based on quantum dots and perovskite films, wherein the infrared up-conversion device based on quantum dots and perovskite films comprises an infrared light spot detector and a perovskite light emitting diode; the infrared light spot detector and the perovskite light emitting diode are connected in series via an intermediate layer, the infrared light spot detector comprises an infrared quantum dot light absorbing layer, and the perovskite light emitting diode comprises a perovskite light emitting layer.

[0007] Another aspect of the present invention provides a method for preparing the infrared up-conversion device based on quantum dots and perovskite film, the method comprising: providing an infrared light spot detector, evaporating an intermediate layer on the infrared light spot detector, and coating a perovskite light emitting diode on the intermediate layer.

[0008] Compared with the prior art, the present invention has the following beneficial effects:

[0009] (1) The photon-to-photon conversion efficiency of the top side can reach more than 10%;

[0010] (2) Achieve higher luminous brightness and can be lit at a lower current density, reducing the operating voltage;

[0011] (3) Metal halide perovskite is used as the light-emitting layer, the preparation method is simple, and the device can also be prepared using a solution method;

[0012] (4) The use of quantum dot infrared absorption layer has low cost, simple process, and the working wavelength is easy to adjust during synthesis;

[0013] (5) The semi-transparent electrode has good transmittance and can be used for large-area top-emission infrared imaging display. It is easy to prepare into a lens or use it directly. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Shown is a schematic structural diagram of an infrared up-conversion device based on quantum dots and perovskite films according to the present invention.

[0015] Figure 2 This is a structural diagram of an infrared up-conversion device based on quantum dots and perovskite films according to Example 1 of the present invention.

[0016] Figure 3 This is a graph showing the luminescence brightness results of an infrared up-conversion device based on quantum dots and perovskite films according to Example 1 of the present invention.

[0017] Figure 4 This is a graph showing the luminescence brightness results of an infrared up-conversion device based on quantum dots and perovskite films according to Example 2 of the present invention.

[0018] Figure 5 This is a graph showing the photon conversion efficiency results of an infrared up-conversion device based on quantum dots and perovskite films according to Example 3 of the present invention.

[0019] Figure 6 This is a graph showing the luminescence brightness results of an infrared up-conversion device based on quantum dots and perovskite films according to Example 3 of the present invention.

[0020] Figure 7 This is an imaging photograph of the infrared up-conversion device when irradiated with infrared light according to Example 3 of the present invention.

[0021] Figure 8 This is a graph showing the luminescence brightness results of an infrared up-conversion device based on quantum dots and perovskite films according to Example 4 of the present invention.

[0022] Fig. 9 This is a graph showing the luminescence brightness results of an infrared up-conversion device based on quantum dots and perovskite films according to comparative example 1 of the present invention.

[0023] Figure 1Description of the accompanying drawings: 1 is a conductive substrate layer, 2 is a first electron transport layer, 3 is an infrared quantum dot absorption layer, 4 is an intermediate layer, 5 is a hole transport layer, 6 is a perovskite light-emitting layer, 7 is a second electron transport layer, 8 is an electron injection layer, and 9 is an electrode. DETAILED DESCRIPTION

[0024] Hereinafter, the infrared up-conversion device based on quantum dots and perovskite film and the method for preparing the same are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0025] At present, the applicant has not found that perovskite is used for up-conversion diode light emission, that is, the perovskite light emitting diode has not been used in combination with an infrared photodetector. The inventor of the present application unexpectedly discovered through a large number of experiments that the photon-to-photon conversion efficiency can be significantly improved by combining an infrared photodetector and a perovskite light emitting diode in series, and the conversion efficiency can reach more than 10%. It is known to those skilled in the art that when quantum dots or perovskites are used alone as light-emitting layers in LEDs, the luminous efficiency itself does not differ much, but the applicant unexpectedly discovered that when used in up-conversion devices, that is, when LEDs (quantum dot light emitting diodes or perovskite light emitting diodes) are used in series with infrared photodetectors, the luminous efficiency of the two is very different (the photon-to-photon luminous efficiency of quantum dot light emitting diodes and infrared photodetectors is only about 1% after being used in series). The applicant believes that this may be related to the influence of energy level structure and carrier transport, that is, the present application overcomes the technical obstacles of the series combination of infrared photodetectors and perovskite light-emitting diodes. Specifically, the barrier of carrier transport is reduced by reasonable energy level matching, and the dense intermediate layer (such as thin MoO3, etc.) is prepared by evaporation, which avoids the corrosion of the lower layer by the solution method solvent and the quenching of the perovskite carrier by the infrared quantum dot absorption layer (such as lead sulfide layer). The flat intermediate interface ensures the smooth crystallization and uniformity of the perovskite, and prepares an infrared up-conversion device based on quantum dots and perovskite films. On this basis, the present application is completed.

[0026] Infrared upconversion devices

[0027] In a first aspect, the present application provides an infrared up-conversion device based on quantum dots and perovskite films, wherein the infrared up-conversion device comprises an infrared light spot detector and a perovskite light emitting diode; the infrared light spot detector and the perovskite light emitting diode are connected in series via an intermediate layer 4, the infrared light spot detector comprises an infrared quantum dot absorption layer 3, and the perovskite light emitting diode comprises a perovskite light emitting layer 6.

[0028] In the infrared up-conversion device provided in this application, if Figure 1 The infrared light spot detector further comprises a conductive substrate layer 1 and a first electron transport layer 2, wherein the first electron transport layer 2 and the conductive substrate layer 1 are sequentially arranged in a direction away from the infrared quantum dot light absorbing layer 3. The intermediate layer 4 is arranged on the infrared quantum dot light absorbing layer 3.

[0029] In the infrared up-conversion device provided in this application, if Figure 1 The perovskite light-emitting diode further comprises a hole transport layer 5, which is disposed between the perovskite light-emitting layer 6 and the intermediate layer 4. A second electron transport layer 7 and an electron injection layer 8 are sequentially disposed on the side of the perovskite light-emitting layer 6 away from the intermediate layer 4, and an electrode 9 is disposed on the electron injection layer 8. The hole transport layer 5 is located above the intermediate layer 4.

[0030] In the infrared up-conversion device provided in the present application, the conductive substrate layer 1 is ITO conductive glass.

[0031] In the infrared up-conversion device provided in the present application, the material of the first electron transport layer 2 is one or more selected from zinc oxide nanoparticles, tin oxide nanoparticles, titanium oxide nanoparticles or C60 and its derivatives. In a specific embodiment, the C60 derivative can be, for example, indene-C60 bisadduct (ICBA).

[0032] In the infrared up-conversion device provided in the present application, the thickness of the first electron transport layer 2 can be, for example, 20-50 nm, 20-30 nm, 30-40 nm, or 40-50 nm, etc. If the first electron transport layer 2 (such as ZnO, etc.) is too thin, it will bring about a large dark current, and if it is too thick, it will bring about a large series resistance.

[0033] In the infrared up-conversion device provided in the present application, the infrared quantum dot light absorbing layer 3 is a quantum dot film, and the quantum dot film is a film after the quantum dots are treated with liquid ligands and / or solid ligands, wherein the surface ligands of the quantum dot film are short-chain ligands containing thiol, amino, halogen, etc. Preferably, the quantum dot film is a PbS colloidal quantum dot film (PbSCQD). It should be noted that, under normal circumstances, the surface of the quantum dots is protected by ligands, and the surface of the general quantum dots contains oleic acid ligands, and oleic acid is a long-chain ligand. In order to improve the mobility, the long-chain ligands need to be exchanged for short-chain ligands.

[0034] In a specific embodiment, the quantum dot film can be processed by liquid ligand exchange (such as Example 1) or solid ligand exchange (such as Example 2), or a double-layer film of liquid phase exchange followed by solid phase exchange (such as Example 3). Among them, liquid ligand exchange, for example, can be mixing the oleic acid ligands on the surface of the PbS quantum dots with an iodine-containing solution for ligand exchange, and then coating it into a film. Solid-state ligand exchange, for example, can be coating the PbS quantum dots into a film first, and then exchanging ligands with ethanedithiol. The liquid and solid in the liquid ligand exchange or solid-state ligand exchange refer to the state of PbS.

[0035] In the infrared up-conversion device provided in the present application, the thickness of the infrared quantum dot light absorbing layer 3 can be, for example, 50-500nm, 50-100nm, 100-300nm, or 300-500nm, etc. If the infrared quantum dot light absorbing layer 3 is too thick, it will bring about a large series resistance, and if it is too thin, it will lead to insufficient light absorption by the light absorbing layer.

[0036] In the infrared up-conversion device provided in the present application, the material of the intermediate layer 4 is one or more selected from molybdenum trioxide, tungsten trioxide or aluminum oxide.

[0037] In the infrared up-conversion device provided in the present application, the thickness of the intermediate layer 4 is 2-10 nm. In some embodiments, the thickness of the intermediate layer 4 can be, for example, 2-5 nm, 5-10 nm, 2-4 nm, 4-6 nm, 6-8 nm, or 8-10 nm. If the intermediate layer 4 is too thin, it will not have a blocking effect, and if it is too thick, it will cause greater carrier quenching.

[0038] In the infrared up-conversion device provided in the present application, the material of the hole transport layer 5 is selected from one or more of poly[bis(4-phenyl)(4-butylphenyl)amine (poly-TPD), 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene (Spiro-OMeTAD), poly(9,9'-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 3-hexyl substituted polythiophene (P3HT), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) or polyvinylcarbazole (PVK).

[0039] In the infrared up-conversion device provided in the present application, the thickness of the hole transport layer 5 can be, for example, 10-30 nm, 10-20 nm, or 20-30 nm, etc. If the hole transport layer 5 is too thin or too thick, it will cause imbalance in carrier injection.

[0040] In the infrared up-conversion device provided in the present application, in some embodiments, the hole transport layer 5 includes a first hole transport layer and a second hole transport layer, wherein the first hole transport layer is arranged above the intermediate layer, and the second hole transport layer is arranged below the perovskite light-emitting layer. In a specific embodiment, the thickness of the first hole transport layer is 10 to 20 nm. The thickness of the second hole transport layer is 10 to 20 nm. The advantage of providing two layers of hole transport layers is to reduce the carrier injection barrier and improve the hole transport capacity.

[0041] Specifically, the material of the first hole transport layer is selected from one or more of poly[bis(4-phenyl)(4-butylphenyl)amine (poly-TPD), 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene (Spiro-OMeTAD), poly(9,9'-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 3-hexyl substituted polythiophene (P3HT), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) or polyvinylcarbazole (PVK).

[0042] The material of the second hole transport layer is selected from one or more of poly[bis(4-phenyl)(4-butylphenyl)amine (poly-TPD), 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene (Spiro-OMeTAD), poly(9,9'-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 3-hexyl substituted polythiophene (P3HT), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) or polyvinylcarbazole (PVK).

[0043] When specifically selected, the materials of the first hole transport layer and the second hole transport layer are different.

[0044] In the infrared up-conversion device provided in the present application, the molecular formula of the perovskite light-emitting layer 6 is (RNH3)2A n- 1B n X 3n+1 , of which RNH3 + It is a large organic cation, wherein the large organic cation is selected from one or more of phenylethylamine, butylamine or phenylbutylamine, the cation at the A position is one or more of Cs, formamidine, and methylamine cations, B is selected from one or more of Pb, Sn, and Ge, X is one or more of I, Br, and Cl, and n is selected from 1 to 10.

[0045] In the infrared up-conversion device provided in the present application, the thickness of the perovskite light-emitting layer 6 can be, for example, 50-100 nm, 50-80 nm, or 80-100 nm, 50-60 nm, 60-70 nm, 70-80 nm, 80-90 nm, or 90-100 nm, etc. The appropriate thickness of the perovskite light-emitting layer 6 can achieve brightness and radiation recombination. Too thick will reduce the radiation recombination efficiency, and too thin will cause greater Auger recombination and reduce brightness.

[0046] In the infrared up-conversion device provided in the present application, the material of the second electron transport layer 7 is selected from one or more of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PyMPM), (1,3,5-triazine-2,4,6-triyl)tris(benzene-3,1-diyl)tris(diphenylphosphine oxide) (PO-T2T) or 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine (TmPyPB), etc.

[0047] In the infrared up-conversion device provided in the present application, the thickness of the second electron transport layer 7 is 30-60 nm, and an appropriate thickness can balance the carrier injection speed. In some embodiments, the thickness of the second electron transport layer 7 can be, for example, 30-40 nm, 40-50 nm, 50-60 nm, etc.

[0048] In the infrared up-conversion device provided in the present application, the material of the electron injection layer 8 is one or more selected from LiF, CsF, or NaF.

[0049] In the infrared up-conversion device provided in the present application, the thickness of the electron injection layer 8 is 1-5 nm. If the electron injection layer 8 is too thick, electrons cannot be injected, and if it is too thin, the film will be discontinuous. In some embodiments, the thickness of the electron injection layer 8 can also be 1-1.2 nm, 1.2-5 nm, 1-3 nm, or 3-5 nm.

[0050] In the infrared up-conversion device provided in the present application, the electrode 9 is a metal electrode, an ITO electrode or a silver nanowire electrode. Optionally, the electrode 9 is a metal electrode. Further optionally, the metal electrode is a translucent metal electrode. Preferably, the translucent metal electrode can be, for example, a double-layer metal electrode; in the double-layer metal electrode, the material of the first layer is selected from one or more of calcium, magnesium or samarium; the material of the second layer is selected from one or more of copper, gold or nickel. More preferably, the translucent metal electrode is selected from a calcium and copper double-layer metal electrode. By setting a translucent metal electrode, on the one hand, the transmittance and light transmittance can be improved, and on the other hand, the conductivity is better.

[0051] In the infrared up-conversion device provided in the present application, the thickness of the electrode 9 is 10 to 25 nm. If it is too thick, it will lead to low transmittance, and if it is too thin, the conductivity is poor. In some embodiments, the thickness of the electrode 9 can be, for example, 10 to 25 nm, 10 to 12 nm, 12 to 15 nm, 15 to 20 nm, or 20 to 25 nm. When a double-layer metal electrode is selected, the thickness of the first layer of the electrode is 6 to 15 nm, and the thickness of the second layer of the electrode is 2 to 10 nm.

[0052] Working principle of the infrared up-conversion device provided in this application (by Figure 1 and 2 For example):

[0053] The infrared quantum dot light-absorbing layer (such as PbS-CQD) receives infrared light. Taking PbS-CQD as an example, its absorption peak is at 1500, which can extend to about 1700 on both sides, and can absorb infrared light. After absorbing infrared light, electron-hole pairs will be generated and transmitted to both sides. The holes will be transmitted to the perovskite light-emitting layer through the middle layer (such as molybdenum trioxide) and the hole transport layer (such as PVK). The electrode (Ca+Cu) injects electrons into the perovskite light-emitting layer through the electron injection layer (LiF) and the second electron transport layer (TPBi). The electrons and holes recombine in the perovskite light-emitting layer and then emit light. In layman's terms, when infrared light irradiates the infrared quantum dot light-absorbing layer (such as PbS-CQD), the perovskite at the corresponding position will emit light.

[0054] In some embodiments, when a mask is added in front of the device, there will be an infrared light-transmitting part and an infrared light-impermeable part. When the patterned infrared light is projected onto the infrared quantum dot light-absorbing layer (e.g., PbS-CQD), visible light of the corresponding pattern can be seen on the other side of the device, for example Figure 7 The part that transmits infrared light is bright, while the part that does not transmit infrared light is dark.

[0055] Preparation method

[0056] The second aspect of the present invention provides a method for preparing an infrared up-conversion device based on quantum dots and perovskite films, comprising: providing an infrared light spot detector, evaporating an intermediate layer on the infrared light spot detector, and coating a perovskite light-emitting diode on the intermediate layer.

[0057] The preparation method provided by the present invention specifically comprises the following steps:

[0058] Obtain an infrared light spot detector through steps a to c, and obtain a perovskite light emitting diode through steps e to i;

[0059] Step a: performing surface treatment on the conductive substrate layer 1;

[0060] Step b: coating the precursor solution of the first electron transport layer on the conductive substrate layer 1 treated in step a, annealing and forming, to obtain the first electron transport layer 2;

[0061] Step c: coating the infrared quantum dot light absorbing layer solution on the first electron transport layer 2 obtained in step b, annealing and forming, to obtain the infrared quantum dot light absorbing layer 3;

[0062] Step d: evaporating an intermediate layer 4 on the infrared quantum dot light absorbing layer 3 obtained in step c;

[0063] Step e: coating the precursor solution of the hole transport layer on the intermediate layer 4 obtained in step d, annealing and shaping, and obtaining the hole transport layer 5;

[0064] Step f: coating the precursor solution of the perovskite light-emitting layer on the hole transport layer 5 obtained in step e, annealing and shaping, and obtaining the perovskite light-emitting layer;

[0065] Step g: evaporating the second electron transport layer 7 on the perovskite light-emitting layer 6;

[0066] Step h: evaporating an electron injection layer 8 on the second electron transport layer 7 obtained in step g;

[0067] Step i: Vapor-depositing an electrode 9 on the electron injection layer 8 obtained in step h to obtain an infrared up-conversion device based on quantum dots and perovskite thin films.

[0068] In the preparation method of the infrared up-conversion device provided in the present application, step a is to perform surface treatment on the conductive substrate layer 1. The surface treatment method may be, for example, plasma or ultraviolet ozone (UVO) treatment on the conductive substrate layer 1. Preferably, the conductive substrate layer 1 is subjected to oxygen plasma treatment, and the treatment time may be, for example, 10 to 20 minutes, 10 to 15 minutes, or 15 to 20 minutes.

[0069] In the preparation method of the infrared up-conversion device provided in the present application, step b is to coat the precursor solution of the first electron transport layer on the conductive substrate layer 1 treated in step a, anneal and form, and obtain the first electron transport layer 2.

[0070] In step b, the concentration of the precursor in the precursor solution of the first electron transport layer is 10-50 mg / mL. In a specific embodiment, the concentration of the precursor in the precursor solution of the first electron transport layer can also be, for example, 10-30 mg / mL, 30-50 mg / mL, 10-20 mg / mL, 20-30 mg / mL, 30-40 mg / mL, 40-50 mg / mL, 10-15 mg / mL, 15-20 mg / mL, 20-25 mg / mL, 25-30 mg / mL, 30-35 mg / mL, 35-40 mg / mL, 40-45 mg / mL, or 45-50 mg / mL, etc. For example, it can be 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 40 mg / mL or 50 mg / mL, etc.

[0071] In step b, the precursor in the precursor solution of the first electron transport layer is one or more of zinc oxide nanoparticles, tin oxide nanoparticles, titanium oxide nanoparticles or C60 and its derivatives. The solvent may be, for example, ethanol.

[0072] In step b, the coating is performed by spin coating, and the spin coating speed may be, for example, 3500-5000 rpm, 3500-4000 rpm, 4000-4500 rpm, or 4500-5000 rpm. The spin coating time may be, for example, 25-60 s, 25-40 s, or 40-60 s. The annealing temperature may be, for example, 800° C.-300° C., 800° C.-600° C., 600° C.-500° C., or 500° C.-300° C. The annealing time may be, for example, 5-20 min, 5-10 min, 10-15 min, or 15-20 min.

[0073] In the preparation method of the infrared up-conversion device provided in the present application, step c is to coat the solution of the infrared quantum dot light absorbing layer on the first electron transport layer 2 obtained in step b, anneal and form, and obtain the infrared quantum dot light absorbing layer 3.

[0074] In step c, the concentration of quantum dots in the solution of the infrared quantum dot light absorbing layer is 100-300 mg / mL. In a specific embodiment, the concentration of quantum dots in the precursor solution of the infrared quantum dot light absorbing layer 3 can be, for example, 100-300 mg / mL, 100-200 mg / mL, 200-300 mg / mL, 100-150 mg / mL, 150-200 mg / mL, 200-250 mg / mL, or 250-300 mg / mL. More specifically, it can be 100 mg / mL, 150 mg / mL, 200 mg / mL, 250 mg / mL or 300 mg / mL.

[0075] In step c, the solution of the infrared quantum dot light absorbing layer 3 is prepared by dissolving lead sulfide quantum dots in a mixed solvent of butylamine and N,N-dimethylformamide (DMF). In a specific embodiment, the volume ratio of butylamine to DMF in the mixed solvent is 3 to 5:1, preferably 4:1.

[0076] In step c, the coating is carried out by a drop coating process, and the drop coating speed may be, for example, 2000-3000 rpm, 2000-2500 rpm, or 2500-3000 rpm. The drop coating time may be, for example, 10-30 s, 10-20 s, or 20-30 s. The annealing temperature may be, for example, 60°C-120°C, 60°C-80°C, 80°C-100°C, or 100°C-120°C. The annealing time may be, for example, 5-20 min, 5-10 min, 10-15 min, or 15-20 min.

[0077] The infrared quantum dot light-absorbing layer 3 obtained in step c has a thickness of 50-500 nm, 50-100 nm, 100-300 nm, or 300-500 nm.

[0078] In the preparation method of the infrared up-conversion device provided in the present application, step d is to evaporate an intermediate layer on the infrared quantum dot light-absorbing layer 3 obtained in step c. After evaporation, a dense intermediate layer is obtained, which avoids the corrosion of the lower layer by the solution method solvent and the quenching of the carriers of the perovskite by the infrared quantum dot light-absorbing layer, and the flat intermediate interface ensures the smooth crystallization and uniformity of the perovskite.

[0079] In step d, the evaporation rate can be, for example, 0.1-1.0 angstrom / second, 0.1-0.5 angstrom / second, 0.5-1.0 angstrom / second, 0.1-0.3 angstrom / second, 0.3-0.5 angstrom / second, 0.5-0.8 angstrom / second or 0.8-1.0 angstrom / second, etc. The sample can be transferred to a coating apparatus for thermal evaporation.

[0080] In step d, the thickness of the intermediate layer can be, for example, 2-10 nm, 2-5 nm, or 5-10 nm.

[0081] In the preparation method of the infrared up-conversion device provided in the present application, step e is to coat the precursor solution of the hole transport layer on the intermediate layer obtained in step d, anneal and shape it, and obtain the hole transport layer 5.

[0082] In step e, the sample usually needs to be transferred to a nitrogen glove box before the coating step, which can isolate water and oxygen and make the material more stable.

[0083] In step e, the preparation of the hole transport layer precursor solution includes: dissolving the precursor of the hole transport layer precursor solution in a meta-xylene solvent. The precursor of the hole transport layer precursor solution is selected from one or more of poly[bis(4-phenyl)(4-butylphenyl)amine (poly-TPD), 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene (Spiro-OMeTAD), poly(9,9'-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 3-hexyl substituted polythiophene (P3HT), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) or polyvinylcarbazole (PVK).

[0084] In step e, the concentration of the precursor in the precursor solution of the hole transport layer is 1 to 16 mg / mL. In a specific embodiment, the concentration of the precursor solution of the hole transport layer can be, for example, 1 to 4 mg / mL, 4 to 10 mg / mL, or 10 to 16 mg / mL. Further, it can be 1 mg / mL, 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL or 16 mg / mL.

[0085] In step e, the coating is performed by spin coating, and the spin coating speed may be, for example, 2000-5000 rpm, 2000-3000 rpm, 3000-4000 rpm, or 4000-5000 rpm. The spin coating time may be, for example, 40-80 s, 40-60 s, or 60-80 s. The annealing temperature may be, for example, 100° C.-150° C., 100° C.-130° C., or 130° C.-150° C. The annealing time may be, for example, 5-15 min, 5-10 min, or 10-15 min.

[0086] In step e, when there are two hole transport layers, the precursor of the first hole transport layer is coated on the intermediate layer 4 obtained in step d, annealed and shaped to obtain the first hole transport layer; then the precursor of the second hole transport layer is coated on the first hole transport layer, annealed and shaped to obtain the second hole transport layer.

[0087] Further, the preparation of the first hole transport layer precursor solution includes: dissolving the precursor of the first hole transport layer precursor solution in a meta-xylene solvent. The precursor of the first hole transport layer precursor solution is selected from one or more of poly[bis(4-phenyl)(4-butylphenyl)amine (poly-TPD), 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene (Spiro-OMeTAD), poly(9,9'-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 3-hexyl substituted polythiophene (P3HT), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) or polyvinylcarbazole (PVK).

[0088] The concentration of the precursor in the precursor solution of the first hole transport layer is 1 to 16 mg / mL. In a specific embodiment, the concentration of the precursor solution of the first hole transport layer can be, for example, 1 to 4 mg / mL, 4 to 10 mg / mL, or 10 to 16 mg / mL. Further, it can be 1 mg / mL, 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL or 16 mg / mL.

[0089] The first hole transport layer is coated by a spin coating process, and the spin coating speed can be, for example, 2000-5000 rpm, 2000-3000 rpm, 3000-4000 rpm, or 4000-5000 rpm. The spin coating time can be, for example, 40-80 s, 40-60 s, or 60-80 s. The annealing temperature can be, for example, 100°C-150°C, 100°C-130°C, or 130°C-150°C. The annealing time can be, for example, 5-15 min, 5-10 min, or 10-15 min.

[0090] Further, the preparation of the second hole transport layer precursor solution includes: dissolving the precursor of the second hole transport layer precursor solution in a meta-xylene solvent. The precursor of the second hole transport layer precursor solution is selected from one or more of poly[bis(4-phenyl)(4-butylphenyl)amine (poly-TPD), 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene (Spiro-OMeTAD), poly(9,9'-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 3-hexyl substituted polythiophene (P3HT), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz) or polyvinylcarbazole (PVK). It should be noted that the selection of the precursor of the first hole transport layer precursor solution is different from the selection of the precursor of the second first hole transport layer precursor solution.

[0091] The concentration of the precursor in the precursor solution of the second hole transport layer is 1 to 16 mg / mL. In a specific embodiment, the concentration of the precursor solution of the second hole transport layer can be, for example, 1 to 4 mg / mL, 4 to 10 mg / mL, or 10 to 16 mg / mL. Further, it can be 1 mg / mL, 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL or 16 mg / mL.

[0092] The second hole transport layer is coated by a spin coating process, and the spin coating speed can be, for example, 2000-5000 rpm, 2000-3000 rpm, 3000-4000 rpm, or 4000-5000 rpm. The spin coating time can be, for example, 40-80 s, 40-60 s, or 60-80 s. The annealing temperature can be, for example, 100°C-150°C, 100°C-130°C, or 130°C-150°C. The annealing time can be, for example, 5-15 min, 5-10 min, or 10-15 min.

[0093] In the preparation method of the infrared up-conversion device provided in the present application, step f is to coat the precursor solution of the perovskite light-emitting layer on the hole transport layer 5 obtained in step e, anneal and fix, and obtain the perovskite light-emitting layer. The preparation method of the perovskite light-emitting layer is simpler, and is prepared in situ on the film.

[0094] In step f, the coating is performed by spin coating, and the spin coating speed may be, for example, 2000-6000 rpm, 2000-4000 rpm, or 4000-6000 rpm. The spin coating time may be, for example, 50-100 s, 50-80 s, or 80-100 s. The annealing temperature may be, for example, 60° C.-100° C., 60° C.-80° C., or 80° C.-100° C. The annealing time may be, for example, 1-10 min, 1-5 min, or 5-10 min.

[0095] In step f, the preparation of the precursor solution of the perovskite light-emitting layer 6 comprises: dissolving the metal salts at the A position and the B position and phenethylammonium bromide in a dimethyl sulfoxide solvent.

[0096] Preferably, the molar ratio of lead bromide, cesium bromide, phenethylamine bromide, 18-crown ether-6 or sodium trifluoroacetate in the precursor solution of the perovskite light-emitting layer 6 in step f is 1: 0.85: 0.15: 0.4: 0.07: 0.13. The concentration of Pb in the precursor solution of the perovskite light-emitting layer is 0.1-1 mmol / mL. In a specific embodiment, the concentration of Pb in the precursor solution of the perovskite light-emitting layer 6 is 0.1-1 mmol / mL, 0.1-0.5 mmol / mL, 0.5-1 mmol / mL, 0.1-0.3 mmol / mL, 0.3-0.5 mmol / mL, 0.5-0.8 mmol / mL, or 0.8-1 mmol / mL, etc. For example, it can be 0.2 mmol / mL, 1 mmol / mL, 2 mmol / mL, 4 mmol / mL, 6 mmol / mL, 8 mmol / mL or 10 mmol / mL, etc. Preferably, the concentration of Pb is 0.2 mmol / mL.

[0097] In the method for preparing the infrared up-conversion device provided in the present application, step g is to evaporate the second electron transport layer 7 on the perovskite light-emitting layer 6;

[0098] In step g, the evaporation rate can be, for example, 0.1 to 5 angstroms / second, 0.1 to 1 angstroms / second, 1 to 3 angstroms / second, or 3 to 5 angstroms / second.

[0099] In step g, the thickness of the second electron transport layer 7 can be, for example, 30 to 60 nm, 40 to 50 nm, 50 to 60 nm, etc.

[0100] In step g, the second electron transport layer is selected from one or more of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine (B3PyMPM), (1,3,5-triazine-2,4,6-triyl)tris(benzene-3,1-diyl)tris(diphenylphosphine oxide) (PO-T2T) or 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine (TmPyPB). In the preparation method of the infrared up-conversion device provided in the present application, step h is to evaporate an electron injection layer 8 on the second electron transport layer 7 obtained in step g.

[0101] In step h, the sample obtained in step g is fed into an organic coating machine to thermally evaporate an electron injection layer 8. The material of the electron injection layer 8 is selected from one or more of LiF, CsF, or NaF.

[0102] In step h, the evaporation rate can be, for example, 0.1 to 5 angstroms / second, 0.1 to 3 angstroms / second, or 3 to 5 angstroms / second.

[0103] In step h, the thickness of the electron injection layer 8 is 1 to 5 nm. In some embodiments, the thickness of the electron injection layer 8 may also be 1 to 1.2 nm, 1.2 to 5 nm, 1 to 3 nm, or 3 to 5 nm.

[0104] In the method for preparing an infrared up-conversion device provided in the present application, step i is to evaporate an electrode 9 on the electron injection layer 8 obtained in step h to obtain an infrared up-conversion device based on quantum dots and perovskite films.

[0105] In step i, the sample obtained in step h is sent into a coating machine to evaporate metal, ITO or silver nanowires to form electrodes.

[0106] In step i, the evaporation rate can be, for example, 0.1 to 1.0 angstrom / second, 0.1 to 0.5 angstrom / second, or 0.5 to 1.0 angstrom / second.

[0107] In step i, the thickness of the electrode 9 is 10-25 nm. In some embodiments, the thickness of the electrode 9 can be, for example, 10-25 nm, 10-12 nm, 12-15 nm, 15-20 nm, or 20-25 nm.

[0108] Optionally, the electrode 9 is a metal electrode. Further optionally, the metal electrode is a semi-transparent metal electrode. Preferably, the semi-transparent metal electrode can be, for example, a double-layer metal electrode; in the double-layer metal electrode, the material of the first layer is selected from one or more of calcium, magnesium or samarium; the material of the second layer is selected from one or more of copper, gold or nickel. More preferably, the semi-transparent metal electrode is selected from a calcium and copper double-layer metal electrode.

[0109] Preferably, in step h, a double-layer electrode is deposited, the thickness of the first electrode is 6-10 nm, and the thickness of the second electrode is 2-6 nm. The first electrode may be Ca, for example, and the second electrode may be Cu, for example.

[0110] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0111] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0112] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0113] The preparation method of zinc oxide nanoparticles in the following examples refers to Shang, Y. et al. Highly stable hybrid perovskite light-emitting diodes based on Dion-Jacobson structure. Sci. Adv. 5, eaaw8072, (2019).

[0114] The preparation method of lead sulfide quantum dots was synthesized by referring to the method in the literature Wang, R. et al. Highly Efficient Inverted Structural Quantum Dot Solar Cells. Adv. Mater. 30, 1704882 (2018).

[0115] Ethanol was purchased from Sinopharm (Shanghai Trial), item number 10009259; chlorobenzene was purchased from Sigma-Aldrich, item number 284513-1L; n-octane was purchased from Aladdin, item number O100578-500ml; acetonitrile was purchased from Aladdin, item number A104443-12×500ml; tetrabutylammonium iodide was purchased from Aladdin, item number T103714-100g; ethanedithiol was purchased from TCI, item number E0 032-25G; toluene was purchased from Sinopharm (Shanghai Trial), item number 10022818; polyTPD was purchased from ADS, item number ADS254BE-1GR25; PVK was purchased from Sigma-Aldrich, item number 368350-5G; lead iodide was purchased from Sigma-Aldrich, item number 900168-5G; sodium trifluoroacetate was purchased from TCI, item number T1336-100G.

[0116] Example 1

[0117] This embodiment provides a specific infrared up-conversion device based on quantum dots and perovskite films.

[0118] The infrared up-conversion device comprises an infrared light spot detector and a perovskite light emitting diode; the infrared light spot detector and the perovskite light emitting diode are connected in series via an intermediate layer 4 .

[0119] The infrared light spot detector comprises a conductive substrate layer 1, and a first electron transport layer 2 and an infrared quantum dot light absorption layer 3 are sequentially arranged above the conductive substrate layer 1 from bottom to top.

[0120] The perovskite light-emitting diode comprises a hole transport layer 5 , on which a perovskite light-emitting layer 6 , a second electron transport layer 7 , and an electron injection layer 8 are arranged in order from bottom to top, and an electrode 9 is arranged on the electron injection layer 8 .

[0121] The conductive substrate layer 1 is ITO conductive glass; the first electron transport layer 2 is a zinc oxide film with a thickness of 30nm; the infrared quantum dot light absorbing layer 3 is a PbS quantum dot film with a thickness of 150nm, and the surface of the PbS quantum dot film contains I -short-chain ligand; the intermediate layer 4 is a MoO3 film with a thickness of 5nm; the hole transport layer 5 is a PVK film with a thickness of 15nm; the perovskite light-emitting layer 6 is an in-situ spin-coated perovskite film with a thickness of 80nm; the second electron transport layer 7 is a TPBi film with a thickness of 40nm; the electron injection layer 8 is a LiF film with a thickness of 1.2nm, and the electrode 8 is a Ca plus Cu electrode with a thickness of 8nm plus 4nm.

[0122] The method for preparing the infrared up-conversion device based on quantum dots and perovskite film specifically comprises the following steps:

[0123] Step a: Place the clean ITO transparent conductive glass in a plasma cleaning machine for 15 minutes and set aside;

[0124] Step b: Preparing the first electron transport layer 2 on the ITO transparent conductive glass:

[0125] Dissolve zinc oxide nanoparticles in ethanol solvent to prepare solution A with a concentration of 20 mg / mL; spin-coat solution A on the ITO transparent conductive glass obtained in step a to prepare a zinc oxide film at a spin-coating speed of 4000 r / min for 30 s, and anneal on a hot plate at 120° C. for 10 min to obtain a first electron transport layer 2;

[0126] Step c: Preparation of infrared quantum dot light absorbing layer 3:

[0127] PbS quantum dots were dissolved in n-octane solution with a concentration of 50 mg / mL to prepare solution B; 1 mL of solution B was diluted to 7 mL with n-octane to prepare solution C; 487 mg of lead iodide and 23 mg of sodium acetate were dissolved in 7 mL of DMF solution to prepare solution D; solutions C and D were mixed in a centrifuge tube, and the solutions were separated after high-speed vortexing for 10 min; the upper clear liquid was discarded, and the lower solution was retained and added with 7 mL of n-octane and vortexed for 1 min. This step was repeated three times and then centrifuged at high speed for 5 min at a centrifugal speed of 4200 r / m in; discard the liquid after centrifugation, dry the obtained solid (exchanged PbS, abbreviated as PbS-I) in a vacuum oven for 5 minutes, and then dissolve it in 200 microliters of a mixed solution of butylamine and DMF (the volume ratio of butylamine and DMF is 4 to 1) to prepare solution E, and the concentration of PbS quantum dots is 250 mg / mL; drip solution E on the first electron transport layer 2 to obtain a liquid phase exchange quantum dot layer, annealing and forming, the dripping speed is 2200 rpm, the dripping time is 20 s, the annealing temperature is 80°C, and the annealing time is 10 min;

[0128] Step d: Preparation of the intermediate layer 4:

[0129] The above sample was transferred to a thermal evaporation coating apparatus to deposit a layer of MoO3 at a deposition rate of 0.3 angstroms / second;

[0130] Step e: Preparation of hole transport layer 5:

[0131] The above samples were transferred into a nitrogen glove box;

[0132] PVK was dissolved in m-xylene solvent with a concentration of 4 mg / ml to prepare solution F, and then solution F was spin-coated on the intermediate layer 4 at a spin-coating speed of 3000 r / min for 60 s, and annealed on a hot plate at 120° C. for 10 min to obtain a hole transport layer 5;

[0133] Step f: Preparation of perovskite light-emitting layer 6:

[0134] 73.4 mg of lead bromide, 36.2 mg of cesium bromide, 3.8 mg of formamidine hydrobromide, 3 mg of 18-crown ether-6 and sodium trifluoroacetate were dissolved in 1 mL of dimethyl sulfoxide solvent to prepare solution G, which was stirred for twelve hours; then solution G was spin-coated on the hole transport layer 5 at a speed of 3000 r / min for 60 s, and annealed on a hot plate at 80° C. for 5 min to obtain a perovskite light-emitting layer 6;

[0135] Step g: Preparation of the second electron transport layer 7:

[0136] The above sample was transferred to a thermal evaporation coating apparatus to deposit a layer of TPBi at a deposition rate of 1 angstrom / second;

[0137] Step h: Preparation of electron injection layer 8:

[0138] The sample was transferred to a thermal evaporation coating apparatus and a layer of LiF was deposited at a rate of 1 angstrom / second;

[0139] Step i: Preparation of semi-transparent metal electrode 9:

[0140] The above sample was placed in a coating machine to evaporate a layer of Ca and Cu at a rate of 0.4 angstroms / second.

[0141] The luminous brightness of the infrared up-conversion device based on quantum dots and perovskite film prepared in Example 1 is as follows: Figure 3 shown.

[0142] The transmittance of the semi-transparent electrode in the semi-transparent infrared up-conversion device is 74.1% at 604nm, and the average transmittance in the visible light range is about 70%.

[0143] Example 2

[0144] This embodiment provides a specific infrared up-conversion device based on quantum dots and perovskite films.

[0145] The difference from Example 1 is that the infrared quantum dot light absorbing layer 3 is composed of 5 layers of PbS quantum dot films, the surface of the PbS film contains thiol short-chain ligands, and the concentration of PbS quantum dots is 50 mg / mL.

[0146] Except for the infrared quantum dot light absorbing layer 3, the thickness of other layers is the same as that of Example 1. The thickness of the infrared quantum dot light absorbing layer 3 is 120 nm. Step c: Preparation of infrared quantum dot light absorbing layer:

[0147] The PbS quantum dots were dissolved in n-octane solution with a concentration of 50 mg / mL to prepare solution B; tetrabutylammonium iodide was dissolved in methanol solution to prepare solution C, wherein the mass fraction of tetrabutylammonium iodide was 10 mg / mL; ethanedithiol was dissolved in acetonitrile solution to prepare solution D, wherein the volume fraction of ethanedithiol was 0.02%; solution B was spin-coated on the electron transport layer prepared in step b, with a spin-coating parameter of 2200 r / min and a time of 10 s; solution C was dropped on the PbS quantum dot film for ligand exchange, reacted for 30 s, and then spin-coated with a spin-coating parameter of 2200 r / min and a time of 10 s, and then methanol was dropped on the PbS quantum dot film for spin-coating cleaning with a spin-coating parameter of 2200 r / min and a time of 10 s to prepare a layer of PbS film; this step was repeated to prepare 4 layers of PbS film; and annealing was performed. Solution B was spin-coated on the lead sulfide layer prepared above, with the spin-coating parameters of 2200 r / min and the time of 10 s; Solution D was dropped on the PbS quantum dot film for ligand exchange, reacted for 30 s, and then spin-coated, with the spin-coating parameters of 2200 r / min and the time of 10 s, and then acetonitrile was dropped on the PbS quantum dot film for spin-coating cleaning, with the spin-coating parameters of 2200 r / min and the time of 10 s, to prepare a layer of PbS film;

[0148] The luminous brightness of the infrared up-conversion device based on quantum dots and perovskite film prepared in Example 2 is as follows: Figure 4 shown.

[0149] Example 3

[0150] This embodiment provides a specific infrared up-conversion device based on quantum dots and perovskite films.

[0151] The difference from Example 1 is that:

[0152] The infrared quantum dot light absorption layer is composed of 5 layers of PbS film, and the surface of the PbS film contains thiol and I-short chain ligands;

[0153] The hole transport layer has two layers, namely the first hole transport layer and the second hole transport layer. The thickness of the first hole transport layer is 15 nm, and the thickness of the second hole transport layer is 15 nm. The thickness of the other layers except the hole transport layer is the same as that of Example 1.

[0154] Step c: Preparation of infrared quantum dot light absorbing layer 3:

[0155] The PbS quantum dots were dissolved in n-octane solution with a concentration of 50 mg / mL to prepare solution B; 1 mL of solution B was diluted to 7 mL with n-octane to prepare solution C; 487 mg of lead iodide and 23 mg of sodium acetate were dissolved in 7 mL of DMF solution to prepare solution D; solutions C and D were mixed in a centrifuge tube, and the solution was separated after high-speed vortexing for 10 min; the upper clear liquid was discarded, and the lower solution was added with 7 mL of n-octane and vortexed for 1 min. This step was repeated three times and then centrifuged at high speed for 5 min at a parameter of 4200 r / min; after centrifugation, the liquid was discarded, and the obtained solid was dried in a vacuum oven for 5 min and then dissolved in 200 microliters of a mixed solution of butylamine and DMF (the volume ratio of butylamine to DMF was 4 to 1) to prepare solution E; solution E was drop-coated on the first electron transport layer 2 to obtain a liquid phase exchange quantum dot layer, and annealed to form, with the drop-coating parameters of 2200 rpm, 20 s, and the annealing parameters of 80°C, 10 min;

[0156] Dissolve ethanedithiol in acetonitrile solution to prepare solution F, wherein the volume fraction of ethanedithiol is 0.02%; spin-coat solution B on the liquid phase exchange layer, the spin-coating parameter is 2200r / min, and the time is 10s; drop solution F on the PbS quantum dot film for ligand exchange, react for 30s, and then spin-coat, the spin-coating parameter is 2200r / min, and the time is 10s, then drop methanol on the PbS quantum dot film and spin-coat it for cleaning, the spin-coating parameter is 2200r / min, and the time is 10s, and a layer of PbS film is prepared;

[0157] Step e: Preparation of hole transport layer 5:

[0158] The above samples were transferred into a nitrogen glove box;

[0159] Poly-TPD was dissolved in chlorobenzene solvent with a concentration of 6 mg / ml to prepare solution G, and then solution G was spin-coated on the intermediate layer at a spin coating parameter of 3000 r / min for 60 s, and annealed on a hot plate at 120° C. for 10 min to obtain the first hole transport layer;

[0160] PVK was dissolved in m-xylene solvent with a concentration of 4 mg / ml to prepare solution H, and then solution H was spin-coated on the intermediate layer with a spin coating parameter of 3000 r / min and a time of 60 s. The solution was annealed on a hot plate at 120° C. for 10 min to obtain a second hole transport layer.

[0161] The photon conversion efficiency of the infrared up-conversion device based on quantum dots and perovskite film prepared in Example 3 is as follows: Figure 5 shown.

[0162] The luminous brightness of the infrared up-conversion device based on quantum dots and perovskite film prepared in Example 3 is as follows: Figure 6 shown.

[0163] Example 4

[0164] This embodiment provides a specific infrared up-conversion device based on quantum dots and perovskite films.

[0165] The difference from Example 3 is that:

[0166] The first electron transport layer 2 is a zinc oxide film with a thickness of 50nm; the infrared quantum dot absorption layer 3 is a PbS quantum dot film, and the surface of the PbS quantum dot film contains I-short chain ligands; the intermediate layer 4 is a MoO3 film with a thickness of 6nm; the hole transport layer 5 is a PVK film with a thickness of 25nm; the perovskite light-emitting layer 6 is a perovskite film with a thickness of 60nm that is in-situ spin-coated; the first electron transport layer 7 is a TPBi film with a thickness of 50nm; the electron injection layer 8 is a LiF film with a thickness of 2nm, and the electrode 8 is a Ca plus Cu electrode with a thickness of 10nm plus 5nm.

[0167] The oxygen plasma treatment time in step a is 10 to 20 minutes.

[0168] In step b, the spin coating speed is 4500 rpm, and the spin coating time is 45 s; the annealing temperature is 140° C., and the annealing time is 15 min.

[0169] In step c, the coating is carried out by a drop coating process, the drop coating speed is 2500 rpm, and the drop coating time is 20 s; the annealing temperature is 120° C., and the annealing time is 10 min; the thickness of the infrared quantum dot light absorbing layer 3 is 120 nm.

[0170] The evaporation rate in step d is 1 angstrom / second;

[0171] In step e, the spin coating speed is 4000 rpm, and the spin coating time is 60 s; the annealing temperature is 70° C., and the annealing time is 20 min.

[0172] Step f: Preparation of perovskite light-emitting layer 6:

[0173] 73.4 mg of lead bromide, 42.6 mg of cesium bromide, and 3 mg of 18-crown ether-6 were dissolved in 1 mL of dimethyl sulfoxide solvent to prepare solution G, which was stirred for twelve hours; then solution G was spin-coated on the hole transport layer 5 at a speed of 4000 rpm for 60 seconds, and annealed on a hot plate at 80° C. for 10 minutes to obtain a perovskite light-emitting layer 6;

[0174] The coating in step g is carried out by evaporation process, and the evaporation rate is 1.5 angstroms / second;

[0175] The coating in step h is carried out by evaporation process, and the evaporation rate is 0.4 angstroms / second;

[0176] The coating in step i adopts an evaporation process with an evaporation rate of 0.4 angstroms / second.

[0177] The photon conversion efficiency of the top-emitting infrared up-conversion device prepared in Example 4 is about 5%.

[0178] The luminous brightness of the top-emitting infrared up-conversion device prepared in Example 4 is as follows: Figure 8 shown.

[0179] Comparative Example 1

[0180] This embodiment provides a specific infrared up-conversion device based on quantum dots and perovskite films.

[0181] The difference from Example 3 is that:

[0182] In step f, CdSe / ZnS luminescent quantum dot solution is used for coating, and the spin coating process is performed with a spin coating speed of 3000 rpm and a spin coating time of 60 s; the annealing temperature is 80° C. and the annealing time is 10 min.

[0183] The photon conversion efficiency of the top-emitting infrared up-conversion device prepared in Comparative Example 1 is about 1%.

[0184] The luminous brightness of the top-emitting infrared up-conversion device prepared in Comparative Example 1 is as follows: Fig. 9 shown.

[0185] from Figure 4 , 5 As can be seen from Figure 7, the infrared up-conversion device can be lit at a very low voltage (2.8V) and can also work at a lower voltage. The traditional up-conversion device made of inorganic materials is generally above 10V. At the same time, the photon conversion efficiency can reach more than 10%, which can achieve more sensitive detection; the wavelength range can be adjusted from 800-2600 nanometers. In addition, the prepared device can be used for large-area imaging, from Figure 8 It can be seen that the ShanghaiTech University logo is accurately restored and displayed in the ultra-large area imaging effect of 3×3cm. In addition, the infrared up-conversion device based on quantum dots and perovskite films has good visible light transmittance, which can ensure charge transport and electron injection while having higher display brightness. It has good application prospects in the fields of infrared detection and imaging devices, biomedical treatment, etc.

[0186] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. An infrared up-conversion device based on quantum dots and perovskite film, characterized in that: The infrared up-conversion device comprises an infrared light spot detector and a perovskite light emitting diode; the infrared light spot detector and the perovskite light emitting diode are connected in series via an intermediate layer (4); the infrared light spot detector comprises an infrared quantum dot light absorbing layer (3); and the perovskite light emitting diode comprises a perovskite light emitting layer (6).

2. The infrared up-conversion device based on quantum dots and perovskite film according to claim 1, characterized in that: The infrared light point detector further comprises a conductive substrate layer (1) and a first electron transport layer (2), wherein the first electron transport layer (2) and the conductive substrate layer (1) are arranged in sequence in a direction away from the infrared quantum dot light absorption layer (3); And / or, the perovskite light-emitting diode further comprises a hole transport layer (5), the hole transport layer (5) being arranged between the perovskite light-emitting layer (6) and the intermediate layer (4), a second electron transport layer (7) and an electron injection layer (8) being arranged in sequence from near to far on a side of the perovskite light-emitting layer (6) away from the intermediate layer (4), and an electrode (9) being arranged on the electron injection layer (8).

3. The infrared up-conversion device based on quantum dots and perovskite film according to claim 1, characterized in that: The material of the intermediate layer (4) is one or more selected from molybdenum trioxide, tungsten trioxide or aluminum oxide; And / or, the thickness of the intermediate layer (4) is 2 to 10 nm.

4. The infrared up-conversion device based on quantum dots and perovskite film according to claim 2, characterized in that: The conductive substrate layer (1) is ITO conductive glass; And / or, the material of the first electron transport layer (2) is one or more selected from zinc oxide nanoparticles, tin oxide nanoparticles, titanium oxide nanoparticles or C60 and its derivatives; And / or, the thickness of the first electron transport layer (2) is 20 to 50 nm; And / or, the infrared quantum dot light absorbing layer (3) is a quantum dot film, which is a film obtained by quantum dots undergoing liquid ligand and / or solid ligand exchange treatment, wherein the surface ligands of the quantum dot film are short-chain ligands containing thiol, amino, halogen, etc.; preferably, the quantum dot film is a PbS quantum dot film; And / or, the infrared quantum dot light absorbing layer (3) has a thickness of 50-500 nm; and / or, the material of the hole transport layer (5) is one or more selected from poly[bis(4-phenyl)(4-butylphenyl)amine, 2,2',7,7'-tetrakis-(dimethoxydiphenylamine)-spirofluorene, poly(9,9'-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], 3-hexyl substituted polythiophene, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid or polyvinylcarbazole; and / or, the hole transport layer (5) has a thickness of 10 to 30 nm; And / or, the molecular formula of the perovskite light-emitting layer (6) is (RNH3)2A n-1 B n X 3n+1 , among which RNH3 + It is a large organic cation, wherein the large organic cation is selected from one or more of phenylethylamine, butylamine or phenylbutylamine, the cation at the A position is one or more of Cs, formamidine, and methylamine cations, B is selected from one or more of Pb, Sn, and Ge, X is one or more of I, Br, and Cl, and n is selected from 1 to 10; And / or, the thickness of the perovskite light-emitting layer (6) is 50 to 100 nm; and / or the material of the second electron transport layer (7) is one or more selected from 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, 4,6-bis(3,5-di(3-pyridyl)phenyl)-2-methylpyrimidine, (1,3,5-triazine-2,4,6-triyl)tris(benzene-3,1-diyl)tris(diphenylphosphine oxide) or 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine; And / or, the thickness of the second electron transport layer (7) is 30 to 60 nm; And / or, the material of the electron injection layer (8) is one or more selected from LiF, CsF, and NaF; And / or, the thickness of the electron injection layer (8) is 1 to 5 nm; And / or, the electrode (9) is a metal electrode, an ITO electrode or a silver nanowire electrode; And / or, the thickness of the electrode (9) is 10 to 25 nm.

5. The infrared up-conversion device based on quantum dots and perovskite film according to claim 4, characterized in that: The metal electrode is a semi-transparent metal electrode.

6. The infrared up-conversion device based on quantum dots and perovskite film according to claim 5, characterized in that: The semi-transparent metal electrode is a double-layer metal electrode; the material of the semi-transparent metal electrode is: the material of the first layer is one or more selected from calcium, magnesium or samarium; the material of the second layer is one or more selected from copper, gold or nickel.

7. A method for preparing an infrared up-conversion device based on quantum dots and perovskite thin films as claimed in any one of claims 1 to 6, the method comprising: An infrared light spot detector is provided, an intermediate layer is evaporated on the infrared light spot detector, and a perovskite light emitting diode is coated on the intermediate layer.

8. The preparation method according to claim 7, characterized in that: Obtain an infrared light spot detector through steps a to c, and obtain a perovskite light emitting diode through steps e to i; Step a: performing surface treatment on the conductive substrate layer (1); Step b: coating the precursor solution of the first electron transport layer (2) on the conductive substrate layer (1) treated in step a, and annealing to obtain the first electron transport layer (2); Step c: coating the infrared quantum dot light absorbing layer (3) solution on the first electron transport layer (2) obtained in step b, annealing and forming, to obtain the infrared quantum dot light absorbing layer (3); Step d: vapor-depositing an intermediate layer on the infrared quantum dot light-absorbing layer (3) obtained in step c; Step e: coating the precursor solution of the hole transport layer (5) on the intermediate layer (4) obtained in step d, annealing and shaping, and obtaining the hole transport layer (5); Step f: coating the precursor solution of the perovskite light-emitting layer on the hole transport layer (5) obtained in step e, annealing and shaping, and obtaining the perovskite light-emitting layer; Step g: evaporating the second electron transport layer (7) on the perovskite light-emitting layer (6); Step h: evaporating an electron injection layer (8) on the second electron transport layer (7) obtained in step g; Step i: Vapor-depositing an electrode (9) on the electron injection layer (8) obtained in step h to obtain an infrared up-conversion device based on quantum dots and perovskite film.

9. The preparation method according to claim 8, characterized in that: In step b, the concentration of the precursor in the precursor solution of the first electron transport layer is 10 to 50 mg / mL; And / or, the concentration of quantum dots in the precursor solution of the infrared quantum dot light absorbing layer (3) in step c is 100-300 mg / mL; And / or, the concentration of the precursor in the precursor solution of the hole transport layer (5) in step e is 1 to 16 mg / mL.

10. The preparation method according to claim 8, characterized in that: The coating in step b adopts a spin coating process, the spin coating speed is 3000-5000 rpm, the spin coating time is 25-60 s; the annealing temperature is 80°C-300°C, and the annealing time is 5-20 min; and / or, the coating in step c adopts a drop coating process, the drop coating speed is 2000-3000 rpm, the drop coating time is 10-30 s; the annealing temperature is 60°C-120°C, and the annealing time is 5-20 min; And / or, the coating in step d is carried out by evaporation process, and the evaporation rate is 0.1 to 1.0 angstroms / second; And / or, in step e, the coating is performed by spin coating, the spin coating speed is 2000-5000 rpm, the spin coating time is 40-80 s; the annealing temperature is 100° C.-150° C., and the annealing time is 5-15 min; And / or, the coating in step f is performed by spin coating, the spin coating speed is 2000-6000 rpm, and the spin coating time is 50-100 s; The annealing temperature is 60°C to 100°C, and the annealing time is 1 to 10 minutes; And / or, in step g, an evaporation process is adopted, and the evaporation rate is 0.1 to 5 angstroms / second; And / or, the coating in step h is carried out by evaporation process, and the evaporation rate is 0.1 to 5 angstroms / second; And / or, the coating in step i is performed by an evaporation process with an evaporation rate of 0.1 to 1.0 angstroms per second.